Development of Improved Characteristic Equations for Lake Rukwa in Tanzania - Valimba, Patrick C. (Tanzania Journal of Engineering and Technology, 2019)
Often Lake Rukwa characteristics have been misreported in literature giving different volumes and surface areas at similar water surface elevations. This study aimed at establishing reliable lake characteristics elevation-area-storage equations for Lake Rukwa by utilising all available data and information to define the bathymetry and derive characteristic equations. A procedure was developed that combines historical lake extents, spot heights from topographical maps and surveyed lake bathymetry to define refined bathymetry to levels it has never reached. It combined spot heights around the lake and selected 13,934 surveyed points (from 107,938 available) within the lake confined by the 820 m land contour boundary and define topographical raster image, which was used to extract lake volumes and surface areas between the lowest point (778 m) and 820 m boundary. Change-point analysis was used to detect segmentation of the elevation-area and elevation-volume relationships, which were fitted to a shifted power model. Contours generated from a refined bathymetry raster indicated Lake Rukwa to comprise two north and south lake basins, which are separated by a ridge lying at an altitude of 794.3 m. The north and south lakes consist respectively of five (5) and three (3) deeper depressions (pools) paralleling the northwest- southeast Konongo Scarp, which are disconnected below altitudes 792 m (north) and 789.4 m (south). Characteristic elevation-area and elevation-volume equations are segmented for lake below ridge altitude (794.3 m) whereas single relationships prevail for a single Lake Rukwa. Comparison of lake volumes estimated by refined and old equations indicated underestimation of lake stored volumes between 782.2 m and 805.65 m altitudes and overestimation thereafter by the old equations although the under/over-estimation remained within 10% between 801 m and 812 m. Old elevation-area equations underestimate lake surface area of up to 796.8 m, thereafter overestimate the lake area up to an altitude of 804.85 m and above this altitude underestimation re-appear. The old equations under/over-estimation, however, remains within 11% for altitudes between 794.3 m and 810 m. The refined equations indicate surface areas of north and south lakes at ridge altitude to be 2,554.4 and 837.1 km2 , respectively forming a 3,391.5 km2 lake while at its highest recorded historical elevation of 804.69 m, Lake Rukwa is 183 km long and 17-51 km wide occupying an area of 5,614.7 km2 (north: 4,409.8 km2; south: 1,204.9 km2) and containing 58.243 km3 of water (north: 44.318 km3; south: 13.925 km3). The developed characteristic equations can be used for water management studies of Lake Rukwa. Keywords: Lake bathymetry; lake characteristic equations; Lake Rukwa; lake surface area; lake stored volume; shifted power models.